PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII - Nupus, Nurhayatun; Armanto, Dian (MES: Journal of Mathematics Education and Science, 2024)
This study aims to determine the effect of the Numbered Head Together learning model on grade VII mathematics learning outcomes as well as the difficulties or weaknesses of students learning by using the Numbered Head Together learning model. This research is quantitative research with experimental research type, the research used pretest-posttest control group design. In this study the population was all class VII students of SMP Negeri 5 Percut Sei Tuan and the sample used consisted of two classes namely VII-6 (experimental class) and class VII-7 (control class). The sampling technique used simple random sampling. Based on the results of the pretest data, the average value of the experimental class was 29.59 and the control class was 31.5. While the posttest results obtained an average experimental value of 77.40 and a control class of 71.34. Based on the results of hypothesis testing using the t-test, it is concluded that there is a significant effect of the Numbered Head Together learning model on the learning outcomes of seventh grade mathematics students at SMP Negeri 5 Percut Sei Tuan. The Numbered Head Together model can reduce students difficulties in understanding and solving linear equations of one variable and increase students’ active participation in learning.